2016
DOI: 10.18632/oncotarget.13713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interrupted time during intensity modulated radiation therapy on survival outcomes in patients with nasopharyngeal cancer

Abstract: ObjectiveTo evaluate the influence of interrupted time (IT) during intensity-modulated radiotherapy (IMRT) on survival outcomes in patients with nasopharyngeal cancer (NPC).Materials and methods515 NPC patients receiving IMRT between January 2007 and December 2011 were retrospectively reviewed. The association of IT with loco-regional failure-free survival (LRFS), progression free survival (PFS) and overall survival (OS) was assessed by univariate and multivariate analysis. The Kaplan–Meier methodology was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Several studies have confirmed the relationship between interruption of CCRT and survival outcome [27][28][29]. Xu et al showed that interruptions of more than four days during radiotherapy were associated with worse progression-free survival and OS in patients with nasopharyngeal cancer [29]. Another study reported by Krusun demonstrated that worse OS was found in the interrupted group compared to the uninterrupted group of patients with cervical cancer who underwent CCRT [27].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies have confirmed the relationship between interruption of CCRT and survival outcome [27][28][29]. Xu et al showed that interruptions of more than four days during radiotherapy were associated with worse progression-free survival and OS in patients with nasopharyngeal cancer [29]. Another study reported by Krusun demonstrated that worse OS was found in the interrupted group compared to the uninterrupted group of patients with cervical cancer who underwent CCRT [27].…”
Section: Discussionmentioning
confidence: 90%
“…Our study showed that interruption of the CCRT is a poor prognostic factor for patients with synchronous ESCC/HNSCC who received CCRT with a curative intent. Several studies have confirmed the relationship between interruption of CCRT and survival outcome [27][28][29]. Xu et al showed that interruptions of more than four days during radiotherapy were associated with worse progression-free survival and OS in patients with nasopharyngeal cancer [29].…”
Section: Discussionmentioning
confidence: 92%
“…Currently, there is a lack of consensus concerning what is considered as prolonged RT or interrupted RT, and the methods to quantify this are heterogeneous. For example, some authors have examined total RT duration, whereas others have examined the number of continuous days that RT was interrupted . Furthermore, the existing published data largely consists of retrospective data that is small in sample size .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some authors have examined total RT duration, whereas others have examined the number of continuous days that RT was interrupted . Furthermore, the existing published data largely consists of retrospective data that is small in sample size . To our knowledge, there is only one published data in a large prospective cohort investigating this question, which is by Yao et al In this study of 447 patients, Yao et al found that RT interruption was significantly associated with locoregional failure survival (LRFS) in the multivariable analysis (HR = 9.64, 95% CI, 4.10–22.65), but RT interruption was not significantly associated with OS in the multivariable model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation